Beliefs, attitudes, and human affairs - Bem, Daryl J. (Belmont, Calif., Brooks/Cole Pub. Co., 1970)
Divides man's beliefs and attitudes into four human activities: thinking, feeling, behaving, and interacting with others.
Includes bibliographical references and index.
Keywords: Belief and doubt